Deterioration of perennial sea ice in the Beaufort Gyre from 2003 to 2012 and its impact on the oceanic freshwater cycle. Issue 2 (22nd February 2014) - Krishfield, R. A.; Proshutinsky, A.; Tateyama, K.; Williams, W. J.; Carmack, E. C.; McLaughlin, F. A.; Timmermans, M.‐L.
Abstract Time series of ice draft from 2003 to 2012 from moored sonar data are used to investigate variability and describe the reduction of the perennial sea ice cover in the Beaufort Gyre (BG), culminating in the extreme minimum in 2012. Negative trends in median ice drafts and most ice fractions are observed, while open water and thinnest ice fractions (<0.3 m) have increased, attesting to the ablation or removal of the older sea ice from the BG over the 9 year period. Monthly anomalies indicate a shift occurred toward thinner ice after 2007, in which the thicker ice evident at the northern stations was reduced. Differences in the ice characteristics between all of the stations also diminished, so that the ice cover throughout the region became statistically homogenous. The moored data are used in a relationship with satellite radiometer data to estimate ice volume changes throughout the BG. Summer solid fresh water content decreased drastically in consecutive years from 730 km3 in 2006 to 570 km3 in 2007, and to 240 km3 in 2008. After a short rebound, solid fresh water fell below 220 km3 in 2012. Meanwhile, hydrographic data indicate that liquid fresh water in the BG in summer increased 5410 km3 from 2003 to 2010 and decreased at least 210 km3 by 2012. The reduction of both solid and liquid fresh water components indicates a net export of approximately 320 km3 of fresh water from the region occurred between 2010 and 2012, suggesting that the anticyclonic atmosphere‐ocean circulation has weakened.